Potential Embolic Sources Differ in Patients With Embolic Stroke of Undetermined Source According to Age: A 15-Year Study - Hou, Yan; Elmashad, Ahmed; Staff, Ilene; Alberts, Mark; Nouh, Amre (Frontiers in Neurology, 2022)
Introduction Understanding the potential embolic source in young patients with ESUS may improve the diagnosis and treatment of such patients. Hypothesis Potential embolic sources (PES) differ in young vs. older patients with ESUS, and, therefore, not all patients with ESUS have the same risk profile for stroke recurrence. Methods Young patients (age 18-49) with ESUS, who were admitted to our stroke center from 2006 to 2019, were identified retrospectively and matched with next consecutive older patients (age 50–99) with ESUS by admission date. PES were categorized as atrial cardiopathy, AFib diagnosed during follow-up, left ventricular disease (LVD), cardiac valvular disease (CVD), PFO or atrial septal aneurysm (ASA), and arterial disease. Patients, who had cancer or thrombophilia, were excluded. The type and number of PES and stroke recurrence rates were determined and compared between young and older patients. Results In young patients (55.3% women, median age 39 years), the most common PES was PFO/ASA, and the rate of other PES was low (2–7%). Half of the young patients (54.1%) had a single PES, only 10% had multiple PES, and 35.3% of young patients did not have any PES identified. In older patients (41.7% women, median age 74 years), the 3 most common PES were atrial cardiopathy (38.1%), LVD (35.7%), and arterial disease (23.8%). Nearly half of older patients (42.9%) had multiple PES. The rate of stroke recurrence tended to be lower in young patients as compared to older patients (4.9 vs. 11.4%, p = 0.29). During a median follow-up of 3 years, only 3 young patients (4.9%) had a recurrent stroke, and two of them had unclosed PFO. There were no recurrent strokes among young patients with no PES identified. Conclusions It was noted that PES differ in patients with ESUS according to age and differences in recurrence. PFO is the only common PES in young patients with ESUS. Future studies prospectively evaluating PES in both age groups are needed.